Venomic, transcriptomic, and bioactivity analyses of pamphobeteus verdolaga venom reveal complex disulfide-rich peptides that modulate calcium channels (2019)
ABSTRACT: Pamphobeteus verdolaga is a recently described Theraphosidae spider from the Andean region of Colombia. Previous reports partially characterized its venom profile. In this study, we conducted a detailed analysis that includes reversed-phase high-performance liquid chromatography (rp-HPLC), calcium influx assays, tandem mass spectrometry analysis (tMS/MS), and venom-gland transcriptome. rp-HPLC fractions of P. verdolaga venom showed activity on CaV2.2, CaV3.2, and NaV1.7 ion channels. Active fractions contained several peptides with molecular masses ranging from 3399.4 to 3839.6 Da. The tMS/MS analysis of active fraction displaying the strongest activity to inhibit calcium channels showed sequence fragments similar to one of the translated transcripts detected in the venom-gland transcriptome. The putative peptide of this translated transcript corresponded to a toxin, here named ω-theraphositoxin-Pv3a, a potential ion channel modulator toxin that is, in addition, very similar to other theraphositoxins affecting calcium channels (i.e., ω-theraphotoxin-Asp1a). Additionally, using this holistic approach, we found that P. verdolaga venom is an important source of disulfide-rich proteins expressing at least eight superfamilies.